Breeding Analysis of Beef Cattle in Madura - Kutsiyah, Farahdilla (Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Breeding of beef cattle in Madura Island is extremely determined by using the best Madura cattle namely Sonok cows and racing bull through selection system with exploiting germ plasm conservation of Madura cattle in Sapudi Island, and improving crossbreeding programme between Madura cattle and exotic cattle. Therefore, there are three points should be done in beef cattle breeding programme in Madura Island. First, selection models by distributing the bull stocks from the central area of Sonok and racing bull cattle or using their liquid/frozen cement to the region thatâs less of good bulls. Second, germ plasm conservation of Madura cattle in Sapudi Island is remained so that must be acted soon because in this time the area has been met Ongole cattle dan their crossbred. Third, crossbreeding program should be settle for the blood proportion of both Madura and sub tropiccal cattle breeds in the some of blood percentage or the contribution of sub tropics blood is in between 25 â 50% tolerated. The most easy way can be established for this policy, F1 is only produced for slaugtering or fattening male and female. Key words: Breeding, Madura cattle, Madura Island